The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12913-022-08167-z
|View full text |Cite
|
Sign up to set email alerts
|

How can big data analytics be used for healthcare organization management? Literary framework and future research from a systematic review

Abstract: Background Multiple attempts aimed at highlighting the relationship between big data analytics and benefits for healthcare organizations have been raised in the literature. The big data impact on health organization management is still not clear due to the relationship’s multi-disciplinary nature. This study aims to answer three research questions: a) What is the state of art of big data analytics adopted by healthcare organizations? b) What about the benefits for both health managers and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…The digitization of cost accounting in the healthcare industry supposes the automation of the accounting processes to facilitate the accomplishment of routine tasks and access to information in real-time on costs [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 82 , 83 ]. In line with the findings of other authors [ 81 , 82 , 83 , 84 ], the paper on the H2 hypothesis revealed the characteristics of the digital technologies implemented in traditional and innovative CAT appreciated by the respondents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The digitization of cost accounting in the healthcare industry supposes the automation of the accounting processes to facilitate the accomplishment of routine tasks and access to information in real-time on costs [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 82 , 83 ]. In line with the findings of other authors [ 81 , 82 , 83 , 84 ], the paper on the H2 hypothesis revealed the characteristics of the digital technologies implemented in traditional and innovative CAT appreciated by the respondents.…”
Section: Discussionmentioning
confidence: 99%
“…BD technology offers several significant advantages for costing tools, particularly in the healthcare industry, given the disadvantages related to the large amounts of information and the complexity of the data collected. In addition to traditional information in a quantifiable form, BD can enhance information using data, images, audio data, and data generated by IoT sensors, including patients [ 6 , 15 , 17 ]. These data are in addition to existing records, providing an opportunity to improve AM practices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations